How to sail - Braden, Twain (Amber Books Ltd, 2017)
SAILING. How to Sail outlines basic sailing techniques for both the beginner and experienced sailor. Whatever your level of ability, this book is packed with useful hints and essential tips that will make sailing a safe, rewarding and enjoyable experience